Implementation of Good Governance in the Ethics-Based Financial Reporting System in the Regional Government of Jember District - Mawahib, Moh. Abil; Fauzan, Fauzan (LifeSciFi, 2026)
In the context of public sector finance, challenges such as lack of transparency, weak accountability, and limited public participation necessitate a reporting system that aligns with ethical and Islamic principles, emphasizing fairness, responsibility, and social relevance. This study examines the development of a Sharia-based financial reporting system with an ethical framework to enhance good governance in the Jember Regency government. This research employs a qualitative approach with a case study method, collecting data through in-depth interviews and document analysis. Findings indicate that implementing a Sharia-based ethical financial reporting system improves accountability, reduces opportunities for corruption, and encourages greater public involvement in financial oversight. The study contributes to public sector governance by demonstrating that integrating Sharia principles with conventional financial reporting can strengthen ethical practices, enhance transparency, and promote responsible management of public resources. These insights provide a practical framework for government institutions seeking to align financial management with ethical and socially responsible standards.